"It's cold here:" Lessons learned from the welcome perceived by newcomers to Brandon, Manitoba. Issue 4 (2nd October 2021) - Lam, Michelle
ABSTRACT: Rural immigration is increasing, but still underrepresented in the literature. What does it mean to welcome well in places without large ethnocultural communities and the diverse range of supports dedicated to settlement and integration? What are the perceptions surrounding newcomer integration, and what experiences are newcomers having outside urban centers? Over the past three years, I used a board game, Refugee Journeys, which uses real-life experiences of newcomers in Canada to launch discussions about inclusion and equity, to conduct focus groups and interviews with newcomers, community leaders, educators, and community members. As someone who grew up in a rural area, I wanted to know if the rosy neighborliness of my childhood would translate to an environment of hospitality, welcome, and inclusion for newcomers, or if the stories told to me by my students over the years – stories of slurs hurled in grocery stores, or exclusion from job opportunities – were closer to the truth. I found a deep disconnect between intentions and impacts, particularly around the topics of language diversity and tolerance. This article describes some of the realities currently experienced by newcomers in Brandon, MB and offers new insights on what it means to settle outside urban areas.